Comparing the social signaling behavior of humpback whales in three group types on the Hawaiian breeding grounds using acoustic tags - Carvalho, Jessica; Lammers, Marc O.; Indeck, Katherine L.; Pack, Adam A.; Castilho, Rita (Frontiers in Remote Sensing, 2022)
Humpback whales (Megaptera novaeangliae) are among the most social of all baleen whale species. While extensive research has been conducted on humpback whale songs, gaps remain in our understanding of other forms of communication, particularly non-song vocalizations. Here, we compare the spectral features and temporal parameters of non-song calls recorded from Acousonde tagged humpback whales in three commonly observed group types in the breeding grounds: adult dyads (N = 3), escorted mother-calf pairs (N = 4), and competitive groups (N = 5). Recordings were collected off Maui, Hawai’i during the winter breeding seasons of 2019-2021. Individual calls were identified based on visual and aural inspection of spectrograms using Raven Pro 1.6 software, with a total of 1,092 calls isolated from 69.6 hours of acoustic recordings. Of the total calls, competitive groups produced 56.7% (over 31.5 hours), escorted mother-calf pairs produced 32.4% (over 22.1 hours), and dyads produced 10.8% (over 15.9 hours), although the difference in call rate (calls/hr/whale) was not statistically significant across groups. Though common social calls were shared across the groups, the temporal parameters and frequencies of calls produced varied significantly (e.g., competitive groups had the shortest inter-call periods, escorted mother calf pairs had the highest frequency calls, and dyads had the longest calls). Our study provides new insights into humpback whale vocal communication behavior in the Hawaiian Islands breeding grounds.